DIVIDENDS AND THE GENERAL CORPORATION STATUTES. - Briggs, L. L. (The Accounting Review, 1933)
The statutory laws governing corporate dividends are significant to accountants and teachers of accounting. The directors of a corporation have power, in their discretion, to determine what, if any, dividends shall be declared and paid to stockholders. This is the general statutory rule which applies in all states and territories of the United States and which also prevails in England. The variations from it are few and slight. The rule applies in New Jersey unless otherwise provided in the certificate of incorporation or in by-laws adopted by at least a majority of the stockholders. In England, a company in general meeting may declare dividends, but the amount must not exceed the amount recommended by the directors. The statutes of several jurisdictions give the stockholders power to exert a limited degree of pressure upon the directors in the matter of dividend declaration. In New Mexico and Puerto Rico in United States, unless otherwise provided in the certificate of incorporation, the directors must declare a dividend of the whole of the company's profits exceeding the reserve and pay it to the stockholders on demand.